2012
DOI: 10.1088/0004-637x/750/2/141
|View full text |Cite
|
Sign up to set email alerts
|

Do Bars Trigger Activity in Galactic Nuclei?

Abstract: We investigate the connection between the presence of bars and AGN activity, using a volumelimited sample of ∼9,000 late-type galaxies with axis ratio b/a > 0.6 and M r < −19.5 + 5logh at low redshift (0.02 ≤ z 0.055), selected from Sloan Digital Sky Survey Data Release 7. We find that the bar fraction in AGN-host galaxies (42.6%) is ∼2.5 times higher than in non-AGN galaxies (15.6%), and that the AGN fraction is a factor of two higher in strong-barred galaxies (34.5%) than in non-barred galaxies (15.0%). Howe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 137 publications
(181 reference statements)
4
52
0
Order By: Relevance
“…This finding may indicate that tidal interactions destroy and/or disfavor bar growth instead of enhancing it as expected from results of numerical simulations. As weak bars are more commonly found in fainter, less-massive galaxies than strong bars (Lee et al 2012b; Cervantes-Sodi et al 2013), the fact that we find the effect of nearby companions at larger scales for the case of weak bars may be not unexpected. Due to the low mass of galaxies hosting weak bars, their gravitational potential is also weaker and they are more fragile to disturbances than their more massive counterparts.…”
Section: Summary and Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This finding may indicate that tidal interactions destroy and/or disfavor bar growth instead of enhancing it as expected from results of numerical simulations. As weak bars are more commonly found in fainter, less-massive galaxies than strong bars (Lee et al 2012b; Cervantes-Sodi et al 2013), the fact that we find the effect of nearby companions at larger scales for the case of weak bars may be not unexpected. Due to the low mass of galaxies hosting weak bars, their gravitational potential is also weaker and they are more fragile to disturbances than their more massive counterparts.…”
Section: Summary and Discussionsupporting
confidence: 63%
“…The large number of strongly barred galaxies in our sample helps to improve the statistics and reduce the statistical errors in our measurements, but even with large error bars, if we look at the result for weakly barred galaxies, we see that the drop of average neighbor counts is noticeable at even larger scales, up to a few hundred kiloparsecs. A possible explanation for this effect at larger scales for the case of weakly barred galaxies might be related with these systems being less massive than those galaxies hosting strong bars (Lee et al 2012b;Cervantes-Sodi et al 2013), which would make them less stable against interactions with massive neighbors even at large separations.…”
Section: Close Neighbor Countsmentioning
confidence: 99%
“…Laine et al 2002). However, Lee et al (2012b) found that no significant difference in bar fraction between active and inactive galaxies can be observed if one compares samples of galaxies that are matched in mass, color, etc.…”
Section: Morphologymentioning
confidence: 97%
“…Observations of the remaining 53 galaxies of the LLQSO sample might be useful to ensure the statistical significance. Lee et al (2012b) analyzed a volume-limited sample of SDSS galaxies with 0.01 < z < 0.05, M r < −20.3 and M * > 10 10 M , similar to our sample. They found a bar-fraction of 41.4% at optical wavelengths.…”
Section: Morphologymentioning
confidence: 99%
“…These shocks are tracing the channels by which the gas flows towards the galaxy centres where it can contribute to the central mass concentration, for example producing star formation, pseudo-bulges formation or AGN activity (e.g. Shlosman, Frank & Begelman 1989;Oh, Oh & Yi 2012;Wang et al 2012;Lee et al 2012). …”
Section: Introductionmentioning
confidence: 99%